2016
DOI: 10.1002/2015jc011468
|View full text |Cite
|
Sign up to set email alerts
|

Pathways and mechanisms of offshore water intrusions on the Espírito Santo Basin shelf (18°S–22°S, Brazil)

Abstract: The pathways and physical mechanisms associated with intrusions of cold, nutrient-rich South Atlantic Central Water (SACW) on the continental shelf of the Espırito Santo Basin (ESB), off southeast Brazil (188S-228S), are investigated. To this end, a set of process-oriented, Primitive-Equation (PE) numerical models are used, together with an independent and more complete PE model, available observations and simple theoretical ideas. SACW enters the model ESB shelf mostly through two preferential pathways along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Wave-dominated shelf, low sediment input, and a seasonal shelf upwelling [20,48] create favorable conditions for the development of extensive RBs. Upwelling along the DRS was also pointed out by many authors [49][50][51], which has been associated to the intrusion of the South Atlantic Central Water (SACW; [45]). Ovalle et al [52] and Palóczy et al [50] found that the temperature near the seabed was lower than 21 • C in many points along the ESCS, pointing out qualitative evidences of the influence of the SACW at this region.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Wave-dominated shelf, low sediment input, and a seasonal shelf upwelling [20,48] create favorable conditions for the development of extensive RBs. Upwelling along the DRS was also pointed out by many authors [49][50][51], which has been associated to the intrusion of the South Atlantic Central Water (SACW; [45]). Ovalle et al [52] and Palóczy et al [50] found that the temperature near the seabed was lower than 21 • C in many points along the ESCS, pointing out qualitative evidences of the influence of the SACW at this region.…”
Section: Discussionmentioning
confidence: 68%
“…Upwelling along the DRS was also pointed out by many authors [49][50][51], which has been associated to the intrusion of the South Atlantic Central Water (SACW; [45]). Ovalle et al [52] and Palóczy et al [50] found that the temperature near the seabed was lower than 21 • C in many points along the ESCS, pointing out qualitative evidences of the influence of the SACW at this region. This oceanographic circulation mechanism is probably one of the most important drivers, along with the sedimentation at this region, affecting the vitality of rhodoliths, at once contributing to the nutrient enrichment of the water and lowering its temperature.…”
Section: Discussionmentioning
confidence: 68%
“…SES is influenced by coastal upwelling during the summer months. Sea surface temperatures range from 24 to 288C, but during deep-water intrusion, bottom temperature can descend to 16.58C on the shelf (Paloczy et al 2016). Chlorophyll a measured during two years in an area situated 40 km north of studied sites at SES ranges from 0.11 to 1.55 lg/l (average 0.47 lg/l) (Costa et al 2014).…”
Section: Introductionmentioning
confidence: 95%
“…Among such relict features, IVs reach up to 600 m widths and extend along 15 km of the cross-shelf gradient, between the 30 m isobath and the shelf break at 70–80 m depth, well within the RB megahabitat ( Fig 1 ) [ 12 , 30 , 31 ]. Shelf waters encompass the interface between hyposaline and turbid Coastal Water nearshore, Tropical Water in the neritic zone, and the south-flowing, warm and oligotrophic Brazil Current along the continental slope, with seasonal upwelling of colder South Atlantic Central Water [ 31 33 ]. Sampling sites are located within a multiple-use Marine Protected Area (MPA), the Costa das Algas Environmental Protection Area, and in the vicinity of a no-take MPA, the Santa Cruz Wildlife Refuge ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%